Personality and psychopathology in relation to severity of alcohol-related problems - Evren, C.; Evren, B.; Dalbudak, E. (Journal of Dependence, 2008)
Objective: The aim of this study was to investigate the relationship between the severity of alcohol use problems and psychopathology and personality dimensions. Method: The study sample consisted of 176 male alcohol-dependent patients who were consecutively hospitalized between December 2005 and July 2006. The Michigan Alcoholism Screening Test (MAST), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Symptom Checklist (SCL-90), and Temperament and Character Inventory (TCI). Findings: The severity of alcohol use problems showed a high level of linear correlation with the severity of depression, anxiety, and overall psychopathology. Among the TCI dimensions, novelty seeking and harm avoidance were linearly correlated with the MATT score, while a negative correlation was found between the MATT dimensions of perseverance, self-directedness, and cooperativeness. High scores on the BAI, low scores on self-directedness, and high scores on novelty seeking were predictors of the severity of alcohol use problems. Conclusion: High scores on novelty seeking, a temperament dimension often associated with alcohol dependence, and low scores on self-management, a character dimension, were also found to be associated with the severity of alcohol use problems. Therefore, when evaluating individuals with alcohol use disorders, novelty seeking and self-management should be considered in addition to anxiety symptoms, as these can be helpful in determining alcohol use severity.
Keywords: psychopathology